Src Activation Aggravates Podocyte Injury in Diabetic Nephropathy via Suppression of FUNDC1-Mediated Mitophagy - Zheng, Ting; Wang, Han-yu; Chen, Yang; Chen, Xiao; Wu, Zi-ling; Hu, Qin-yu; Sun, Hui (Frontiers in Pharmacology, 2022)
Background and purpose: Mitophagy plays a significant role in the progression of diabetic nephropathy (DN), although the regulatory mechanisms remain unclear. Recently, accumulating evidence demonstrated that impaired mitochondrial function and mitophagy are involved in DN. Here, we are aimed to explore the role of c-Src (Src) and FUNDC1-related mitophagy in the development of DN. Methods: The db/db mice were used to establish a DN mice model. The mice accepted PP2 (Src inhibitor) treatment to study the role of Src in DN. Kidney function was measured via biochemical testing. Renal histopathology and morphometric analysis were conducted via hematoxylin-eosin (HE), periodic acid-Schiff (PAS), Masson’s staining, and transmission electron microscopy (TEM). We measured degree of apoptosis in kidney by TUNEL assay. Indices of mitophagy (LC3 and p62) were evaluated by Western blotting and immunofluorescence. Complementary in vitro assays were conducted using human podocytes subjected to high glucose in combination with PP2 treatment or FUNDC1 small interfering RNAs (siRNAs). Flow cytometry was used to detect the apoptotic cells. Mitochondrial function was evaluated by JC-1 staining. Double immunofluorescence labeling of LC3 and TOMM20 used to assess the degree of mitophagy. Results: Increased Src activation was detected in the kidneys of db/db mice, and its expression was positively correlated with mitochondrial damage, podocyte apoptosis, and renal dysfunction. Inhibition of Src activation with PP2 protected against mitochondrial damage and podocyte apoptosis. In vitro experiments in podocytes established that high glucose increased Src activation, promoting FUNDC1 phosphorylation and inhibiting mitophagy. Consistent with the mouse model, inhibiting Src activity protected podocytes against mitochondrial damage. FUNDC1 silencing negated the actions of PP2, indicating that FUNDC1-mediated mitophagy is downstream pathway of Src. Conclusion: In summary, our data indicated that Src is a culprit factor in diabetic renal damage via suppression of FUNDC1-mediated mitophagy, promoting the development of DN.